2012
DOI: 10.1002/jso.23282
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of CAII is associated with tumor differentiation and poor prognosis in patients with pancreatic cancer

Abstract: This study suggests the clinical significance of CAI, CAII and p53 expression in pancreatic cancer and provides evidence for AZ as a potential target for controlling pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…In general, one of the most important roles of retinoids is a fine regulation of differentiation both in normal and pathological states [22]. It has been recently shown that a down-regulation of the differentiation marker CA2 is associated with a poor prognosis of patients with PDAC [26]. Our data also point out the importance of CA2 for the prediction of OS of PDAC patients.…”
Section: Link Between Retinoids As Well As Their Receptors and Emt Csupporting
confidence: 70%
“…In general, one of the most important roles of retinoids is a fine regulation of differentiation both in normal and pathological states [22]. It has been recently shown that a down-regulation of the differentiation marker CA2 is associated with a poor prognosis of patients with PDAC [26]. Our data also point out the importance of CA2 for the prediction of OS of PDAC patients.…”
Section: Link Between Retinoids As Well As Their Receptors and Emt Csupporting
confidence: 70%
“…Furthermore, earlier observations of the acid response of store-operated calcium entry (64) and mTORC1 (65) were made in the absence of CO 2 /HCO 3 Ϫ , arguing for H ϩ ions as the key regulators. Growing evidence points to a negative correlation between the expression of CA i isoforms, such as CAII, and cancer disease severity (11,(13)(14)(15). Importantly for disease progression, CAII down-regulation would help to protect cytoplasmic pH from pCO 2 fluctuations and bestow cancer cell pH with a greater degree of autonomy from extracellular influences, such as those arising from intermittent blood flow (73).…”
Section: Discussionmentioning
confidence: 99%
“…The dismal prognosis of pancreatic cancer has been linked to poor tumor differentiation (2, 3), a widely accepted index for prediction of therapeutic response and prognosis of many cancers including pancreatic cancer. Despite significant clinical implications, however, the molecules and signaling pathways that regulate the differentiation of pancreatic cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%